RESONANSI BLACK LIVES MATTER DI AUSTRALIA - Alexandra, Frisca; Daniah, Rahma (Interdependence Journal of International Studies, 2020)
In 2020, the Black Lives Matter movement has gained the attention of international society. The movement that started in the United States is now resonating in Australia. Australia itself has a long history of racial discrimination against Aborigines. Even though the Australian government has formally apologized for its racial discrimination policies in the past and made a number of efforts to improve the lives of Aborigines, in fact, the lives of Aborigines are still far from prosperous. Even the death rate of Aborigines in prison is the highest in the world. Using the New Social Movement Theory, the author analyzes that social conditions in Australian society have created a dominant conflict, this is what causes the Black Lives Matter movement resonate in Australia. Through Amartya Sen’s thoughts, the author provides a solution that is expected to be able to stop various acts of racial discrimination.